Spatial Heterogeneity of Steppe Bird Community in the Azov-Black Sea Enclave of the European Dry-Steppe Zone (Southern Ukraine) - Yu. O. Andryushchenko (Zoodiversity, 2022)
Over the period 2007–2019, the author’s censuses of steppe birds in the Azov-Black Sea dry-steppe enclave determined five species as dominants and co-dominants by their abundance. Thus, Melanocorypha calandra dominates throughout the whole area, Emberiza calandra dominates in 4 subregions and co-dominates in 5 subregions, Motacilla feldegg, Emberiza hortulana, Anthus campestris, Alauda arvensis dominate in 1 subregion and do not dominate or co-dominate in 1–4 subregions. There is a general increasing trend in the total abundance of steppe birds and the number of their rare breeding species from north-west to south-east, whereas the number of their dominants and co-dominants grows in the opposite direction. According to the list, the correlation between the dominants/co-dominants and the number of rare breeding steppe species, it was revealed that the most valuable for the support of the steppe bird populations are subregions with the largest areas of virgin steppes (the Kerch Peninsula, Western and Central Crimea). The least important are the subregions with the highest degree of anthropogenic transformation (northern part of the Syvash region, western part of the Black Sea region) and the Lower Dnipro wetlands. Therefore, it is a high abundance of steppe birds and the maximum number of rare steppe species which should be a specific ornithological indicator of the status of zonal landscapes in the dry steppe zone (especially within protected natural areas of Ukraine) rather than general avian species diversity including introduced, invasive species, synanthropes, etc.